The role of the hybrid-specific technological recommendations of maize in precision crop production procedures - Széll, Endre; Makra, Máté (Acta Agraria Debreceniensis, 2012)
The necessity of application of hybrid specific crop production technology has been confirmed not only by trial results but also by the experiences gained from the agricultural practice. For this reason it is essential to test and collect data in field trials about the specific agronomic traits of the corn hybrids belonging to different maturity groups and genotypes. Corn hybrids are tested for their responses to sowing time, plant density and fertilizer supply; sensitivity to herbicides; and lately, the resistance to the damages caused by the larvae of corn root worm. Last but not least, mention should be made of the differences in the responses of the corn hybrids to the damages caused by drought stress. Based on the trial results, suggestions for the hybrid specific corn production are compiled and made public for the experts and farmers engaged in corn growing. Corn hybrids may deliver maximum yields on the impact of specific crop production technology only in case if it relies on carefully done general production technology including soil cultivation, seed bed preparation and weed control. Similarly, precision crop production technology may advance the yield increase in economic way if it is constantly drawing on the source of research results.